Kecemasan Caregiver dalam Pengasuhan Pasien Skizofrenia: Sebuah Studi Kualitatif tentang Beban Pengasuhan - Maulidiyah Junnatul Azizah Heru; Jatimi, Atika; Antonia Reong (Universitas Nazhatut Thullab Al- Muafa Sampang, 2025)
Introduction: Schizophrenia is a serious mental disorder that not only affects patients but also has a significant impact on caregivers who provide care. Objectives: This study aims to explore the anxiety experienced by caregivers of schizophrenia patients. Methods: Using a qualitative approach with a phenomenological design, this research involved 10 caregivers caring for schizophrenia patients in the Pajarakan Health Center area, Probolinggo Regency. Data was collected through in-depth interviews, and analysis was conducted using the Coalizzi method. Results: The results show that caregiver anxiety is influenced by limited social support, social stigma related to mental illness, and high economic burden. In addition, emotional stress and feelings of helplessness also play an important role in shaping their anxiety. Conclusions: The anxiety experienced by caregivers of schizophrenia patients is influenced by interrelated social, economic, and psychological factors. A lack of social support and the stigma attached to mental illness exacerbate psychological conditions, while economic burdens add emotional pressure.